Values Of Islamic Religious Education In Tarekat Teachings - Ahmad Fahrowi (MAQOLAT: Journal of Islamic Studies, 2023)
Old age is a time when everyone will pass it. The aging process means a decrease in physical endurance, resulting in changes in the structure and function of cells, tissues and organ systems. Decreased physical endurance results in aging cognitive development with marked cognitive decline including: forgetfulness, memory not functioning properly. In addition, old age needs to adjust to the death of a spouse and prepare itself to face death. One of the most well-known congregations in Indonesia with the largest number of followers is the Tarekat Qadiriyah wa Naqsabandiyah with various teachings and methods used, as in Larangan Village, Loh Beneficial District, Indramayu Regency. Not a few residents who follow the tarekat where many of them are elderly. This activity is held every Monday at the Miftahussudur mosque. This study aims to find out how the teachings are taught in the tarekat qodiriyah wa naqsyabandiyah and to find out how the implementation of the tarekat Qodiriyah wa Naqsyabandiyah is implemented in Larangan Village, Loh Beneficial District, Indramayu Regency, and its influence on the elderly. The conclusion of this study is that the values of Islamic religious education in the teachings of the tarekat, namely, 1) the values of Islamic religious education in the teachings of the tarekat are creed, sharia, morals. 2) Implementation of the implementation in the tarekat Qodiriyah wan Naqsabandiyah in the form of reciting dhikr which is practiced every time by the congregation and reciting dzikir which is read every fardhu prayer, besides that there is also another practice, namely reading the Al-Qur'an every day, 3) the influence of the teachings tarekat in daily life in the form of the hearts of the congregation become calm, more and more solemn in carrying out prayers, more prepared in the face of death.